2019
DOI: 10.19044/esj.2019.v15n7p129
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Factors that Induce Premarital Sexual Intercourse Among Adolescents in Secondary Schools in Nigeria

Abstract: Adolescence is a period of life that is characterized by dramatic changes in biological processes in physical and social contexts. The period can be demanding and challenging because adolescents are preoccupied with self-identity, self-image and acceptability in the society as well as selfawareness since the action to be taken is a big part of person's life in the future particularly on whether or not to engage in premarital sexual intercourse. This study investigated factors that induce adolescents to engage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Abdissa, Addisie and Seifu (2017) sexual behaviours include poor socio-economic status, environment, harmful traditional practices, low contraceptive use and voluntary counseling and testing utilization. Olusegun (2019) observed that one of the factors contributing to involvement in sexual activities is peer pressure that is, adolescents' desire to belong with their peers. Adolescents who perceive their peers to be sexually active will likely engage in same to remain acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Abdissa, Addisie and Seifu (2017) sexual behaviours include poor socio-economic status, environment, harmful traditional practices, low contraceptive use and voluntary counseling and testing utilization. Olusegun (2019) observed that one of the factors contributing to involvement in sexual activities is peer pressure that is, adolescents' desire to belong with their peers. Adolescents who perceive their peers to be sexually active will likely engage in same to remain acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Organisasi Kesehatan Dunia (WHO) memperkirakan bahwa 20% orang yang hidup dengan HIV/AIDS berusia 20an tahun dan satu dari dua puluh remaja tertular IMS setiap tahunnya (Olasode, 2007). Beberapa faktor yang mempengaruhi perilaku seksual berisiko pada remaja yang pada akhirnya berakibat pada infeksi menular seksual, yaitu usia, jenis kelamin, tempat tinggal, sikap, pendidikan, pengetahuan, peran media, gaya hidup, dan pengaruh teman sebaya (Olusegun, 2019).…”
Section: Pendahuluanunclassified